Pendistribusian Zakat Dalam Perspektif Amanah Pada BAZNAS Provinsi Gorontalo - Pausther, Kartika Fatmawati; Niswatin, Niswatin; Rasuli, La Ode (IAIN Kudus, 2021)
This study aims to determine the zakat distribution with trust perspective in BAZNAS of Gorontalo Province with qualitative method. Trustworthiness is trustworthy, but several indicators serve as benchmarks for achieving it, including responsibility, keeping promises, and being transparent. The results showed that the BAZNAS of Gorontalo Province had carried out its duties in the distribution of zakat in a trustworthy manner; 1) responsible for overseeing the management of zakat based on legal compliance, Islamic law, trustworthiness, integrity, accountability, and justice; 2) trustworthy, reviewed based on timeliness, object, and implementation; 3) transparent, where all information can be accessed on the official website of BAZNAS. Hopefully, the study results can be a literature review for interested parties. Keywords: Distribution; Zakat; Amanah Perspective; BAZNAS of Gorontalo Province